2013
DOI: 10.1016/j.ijgo.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Does integrating family planning into HIV care and treatment impact intention to use contraception? Patient perspectives from HIV‐infected individuals in Nyanza Province, Kenya

Abstract: Objective To evaluate whether HIV-infected women and men in HIV care and not using highly effective methods of contraception thought they would be more likely to use contraception if it were available at the HIV clinic. Methods A face-to-face survey assessing family-planning knowledge, attitudes, and practices was conducted among 976 HIV-infected women and men at 18 public-sector HIV clinics in Nyanza, Kenya. Data were analyzed using logistic regression and generalized estimating equations. Results The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…The predominance of age lower than 39 years, steady relationship, and low household income among the study participants showed that women of reproductive age and socio-economic vulnerability were exposed to the virus through sexual transmission, in conformity with other studies (4,(12)(13) . According to the current research, after diagnosis women with HIV/AIDS continued working actively to guarantee the income of their children and partners (14) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The predominance of age lower than 39 years, steady relationship, and low household income among the study participants showed that women of reproductive age and socio-economic vulnerability were exposed to the virus through sexual transmission, in conformity with other studies (4,(12)(13) . According to the current research, after diagnosis women with HIV/AIDS continued working actively to guarantee the income of their children and partners (14) .…”
Section: Discussionsupporting
confidence: 89%
“…It should be mentioned that these same clinical characteristics were also found among African women (14)(15) . Considering that the discovery of infection among the current study participants took place during a prenatal examination, more than half of the women with HIV/ AIDS already had one or two children at the time of the interview, a number similar to that found in other studies (10,(13)(14) . Evidence shows that maternity is an important motivation for women with HIV/AIDS to continue with their life plans and adhere to the treatment (15) .…”
Section: Discussionsupporting
confidence: 83%
“…This was a similar finding among men at the non-integrated sites in the CRT as well. 15 The men strongly identified with their HIV care clinic and its providers over the MCH clinics. Integration of FP and HIV services is occurring at several types of facilities in SSA, not just at HIV care clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The unmet need for FP services is particularly high in Kenya; one study found that nearly 70% of HIV-positive women in western Kenya indicate wishing to delay their fertility for another 2 years or not have any further children. 15 Yet, among this same population, only 19% of the women reported the use of more effective contraception (defined as hormonal methods, intrauterine devices (IUDs), and permanent methods). 16 Two systematic reviews have now demonstrated that integrating FP and HIV services is feasible and has varying degrees of positive health outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation